2018
DOI: 10.31234/osf.io/3nr9v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of content and intensity of thought on behavioral and pupil changes during active mind wandering, off focus and on-task states

Abstract: Mind wandering (MW) is a pervasive phenomenon that occurs very frequently regardless of the task. A content-based definition of MW holds that MW occurs when the content of thought switches from an on-going task and/or external stimulus-driven event to self-generated or inner thoughts. A recent account suggests that the transition between these different states of attention occurs via an off-focus state. Following this suggestion, previous work relating MW to pupil size might have lumped attentional states that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…In contrast, Konishi et al [47] found that in non-clinical samples, negative and intrusive thoughts were associated with smaller baseline pupil size [48]. One recent study investigated how the "intensity" of experienced thought was reflected in baseline pupil size, which may be a dimension somewhat comparable to the stickiness of the thought [41]. However, that study was unsuccessful in finding an effect of intensity of thought in baseline pupil size.…”
Section: Correlates Of Self-generated Thought and Stickiness In Pupilmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, Konishi et al [47] found that in non-clinical samples, negative and intrusive thoughts were associated with smaller baseline pupil size [48]. One recent study investigated how the "intensity" of experienced thought was reflected in baseline pupil size, which may be a dimension somewhat comparable to the stickiness of the thought [41]. However, that study was unsuccessful in finding an effect of intensity of thought in baseline pupil size.…”
Section: Correlates Of Self-generated Thought and Stickiness In Pupilmentioning
confidence: 96%
“…The magnitude of this response has been demonstrated to depend on the amount of attention, cognitive control, and cognitive processing required by the task [36][37][38]. Research has consistently found that when we engage in selfgenerated thought, our evoked responses in pupil size are smaller [33,[39][40][41]. Smallwood and colleagues [15] interpreted this smaller response in pupil size as evidence that external processing is being inhibited during self-generated thinking, so-called perceptual decoupling.…”
Section: Correlates Of Self-generated Thought and Stickiness In Pupilmentioning
confidence: 99%
“…SCANPATH AND MIND-WANDERING 5 reduced cortical response to both the target and the sudden onset of the distractor (as measured by the P3 and P1 event-related potential component) during mind-wandering compared to when being on-task. Other studies have similarly found that MW was associated with an attenuation of perceptual processing, as measured by event-related potentials (Barron et al, 2011;Braboszcz & Delorme, 2011;Smallwood, Beach, et al, 2008), task-evoked pupillary responses (Jubera-García et al, 2019;Unsworth & Robison, 2016, 2016, and brain activation patterns (Fox et al, 2015). Perceptual decoupling has been suggested to play a functional role in protecting the continuity and integrity of the internal train of thought by minimizing perceptual interference (Smallwood, 2013).…”
Section: Refixation Patterns Of Mind-wandering During Real-world Scenmentioning
confidence: 93%
“…In the first two analysis, we validated the subjective response to the thought probes by looking at their relation to objective markers of MW. First, we looked at the reaction time coefficient of variance (RTCV) that has been consistently shown to be related to MW (Bastian & Sackur, 2013;Cheyne, Solman, Carriere, & Smilek, 2009;Groot et al, 2021;Jubera-García, Gevers, & Van Opstal, 2020). The RTCV was calculated by taking the standard deviation of eight trials before a thought probe (excluding error trials and no-go trials), divided by their mean.…”
Section: Figure 1 (A) Evening Chronotypes Mind-wander More Compared To Morning and Intermediate Chronotypes (B)mentioning
confidence: 99%